Laparoscopic Ureteral Reimplantation in Endometriosis: A Severe Case - Tchartchian, Garri; Fabricius, Paul G.; Bojahr, Bernd; De Wilde, Rudy L. (The Surgery Journal, 2017)
In aggressive cases, endometriosis can perturb the urogenital tract, in particular the ureter, which can potentially result in ureteral compression or stenosis. Even though this is rare, consequences are dramatic, such as hydronephrosis or organ failure. The present standard intervention comprises the resection of affected tissues and endometriosis foci combined with adjuvant hormonal therapy. When the ureter does not recover, ureteral reimplantation is required. The present case describes the successful laparoscopic approach of the reimplantation of the ureter with simultaneous cystoscopy.
Keywords: endometriosis; laparoscopy; ureteral reimplantation